2019
DOI: 10.1002/ijc.32490
|View full text |Cite
|
Sign up to set email alerts
|

Prospective observation: Clinical utility of plasma Epstein–Barr virus DNA load in EBV‐associated gastric carcinoma patients

Abstract: Epstein–Barr virus (EBV)‐associated gastric carcinomas (EBVaGCs) may account for 8–9% of all gastric cancer (GC) patients. All previous reports on EBVaGC were retrospective. Prospective study is warranted to evaluate the exact role of EBV status in predicting the prognosis of GC. It is of special interest to figure out whether dynamic detection of plasma EBV‐DNA load could be a feasible biomarker for the monitor of EBVaGC. From October 2014 to September 2017, we consecutively collected GC patients (n = 2,760) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 36 publications
3
33
1
Order By: Relevance
“…To date, the EBV infection status of ICC in southern China, with the highest incidence of EBV-associated NPC [12], still remains unknown. Our results revealed for the first time that the overall prevalence of EBVaICC was 6.6%, which was similar to that of EBVaGC (5.1%) in this area [7]. In addition, all EBVaICCs were positive for EBNA1, without immunostaining for LMP1 and EBNA2, which indicated that EBV harbored in ICC was a latency type I infection.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…To date, the EBV infection status of ICC in southern China, with the highest incidence of EBV-associated NPC [12], still remains unknown. Our results revealed for the first time that the overall prevalence of EBVaICC was 6.6%, which was similar to that of EBVaGC (5.1%) in this area [7]. In addition, all EBVaICCs were positive for EBNA1, without immunostaining for LMP1 and EBNA2, which indicated that EBV harbored in ICC was a latency type I infection.…”
Section: Discussionsupporting
confidence: 75%
“…Epstein-Barr virus (EBV) has been linked to several carcinomas of the aerodigestive tract, especially undifferentiated nasopharyngeal carcinoma (NPC) [6] and EBV-associated gastric carcinoma (EBVaGC) [7], but the relationship between EBV infection and ICC pathogenesis has not been well characterized. The current level of evidence on EBV-associated ICC (EBVaICC) is solely based on case reports and small series [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In a 2019 large prospective study of 2760 gastric cancer patients, 52.1% (73/140) of EBV-associated gastric carcinomas had detectable EBV-DNA. 135 Furthermore, the plasma EBV-DNA load was found to be associated with treatment response, with the load decreasing in responders but increasing with disease progression.…”
Section: Virus-specific Dna Elementsmentioning
confidence: 99%
“…By measuring immune-related proteins in plasma of patients with EBV-positive tumors and EBV-negative tumors, Camargo et al found some chemokines and PD-L1 in plasma that could be used for the diagnosis of EBV status [165]. The plasma EBV-DNA load in EBVaGC patients decreases when the patients show response to the treatment, while load increases when the disease progresses, suggesting that plasma EBV-DNA serves as an ideal marker in predicting recurrence and chemotherapy response [166].…”
Section: The Diagnosis and Treatment Of Ebvagcmentioning
confidence: 99%